Quantifying soybean biological nitrogen fixation using long-term isotope enrichment - Ophelia Tsai; Steven J. Hall; George L. Graef; Luis G. Posadas; James E. Specht; William G. Crumpton; Matthew J. Helmers; Shawn P. Conley (Plant and Soil, 2026)
Background and aims Biological nitrogen fixation (BNF) supplies much of soybean ( Glycine max (L.) Merr.) nitrogen (N) demand, but reported fixation rates vary widely, leading to uncertainty in the soybean N cycle. We quantified whole-plant soybean BNF and N allocation using long-term 15 N labeling to assess whether BNF can offset grain N removal in a high-yielding system, and to quantify root contributions to fixed N. Methods Field mesocosms in Iowa, USA received three legacy fertilizer N rates as 2 atom% 15 N-enriched urea for four prior seasons of maize ( Zea mays L.) production. In 2024, N-fixing and non-N-fixing soybeans were grown to physiological maturity. Grain, aboveground biomass, and roots were analyzed to quantify BNF and to estimate whole-plant N budget. Results Soybean derived 81.8% ± 1% (SE) of total plant N from BNF. Legacy N rate had no effect on whole-plant N accumulation, BNF, or N partitioning among tissues (p > 0.05). Roots contained ~2% of total fixed N, with most BNF-derived N allocated to grain. High grain N removal was largely offset by BNF (174.7 ± 8.9 kg N ha −1 ), resulting in a near-neutral partial N balance (−5.7 ± 2 kg N ha⁻ 1 ). Conclusion From this one-season mesocosm study, our finding of negligible fixed N in soybean roots indicates that neglecting root BNF does not necessarily bias conclusions about soybean N cycle. However, the combination of long-term isotope labeling and non-nodulating isolines yielded much less variable and higher BNF rates than previous studies, suggesting the possibility of underestimation for soybean BNF in historical studies.

Identifying cognitive subgroups in older adults from community data with hierarchical cluster analysis - J. D. Hall; Yilin Liu; Jacob Green; Reyna Hickey; Emily C. Edmonds; Steven Z. Rapcsak; Ying-Hui Chou (GeroScience, 2026)

Mineral-associated organic carbon dominance and persistence in coastal wetlands - Yanqi Xiao; Steven J. Hall; Aaron Thompson; Jialin Wang; Jingxuan Chen; Yilin Lan; Cong-Qiang Liu; Chunmei Chen (Geochimica et Cosmochimica Acta, 2026)

Heparin-incorporated whey protein isolate-derived hydrogels with an intended dual function as snakebite wound dressings and drug delivery systems inhibit spitting cobra venom-induced cytotoxicity - Matthew J. Gray; Daniel K. Baines; Gabrielle De Castro; Thomas Cobb; Layla A. Tyrrell; Sam J. Hyam; Alan M. Smith; Nicholas R. Casewell; Sarah L. Allinson; Timothy E.L. Douglas; Steven R. Hall (Toxicon, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

A history of the collaborative group of the Americas on inherited gastrointestinal cancer (CGA-IGC): 1995–2025 - Beth Dudley; Bruce M. Boman; Marc S. Greenblatt; Steven H. Erdman; Paul E. Wise; Randall E. Brand; Carol A. Burke; Jose G. Guillem; Michael J. Hall; Heather Hampel; Brandie Heald; Matthew F. Kalady; et al. (Familial Cancer, 2026)

Towards a global barcode reference library for subterranean fauna - Michelle T. Guzik; Jake Thornhill; Mieke van der Heyde; Danielle N. Stringer; Nicole E. White; Mattia Saccò; Perry G. Beasley-Hall; Paul Nevill; Rachael A. King; Steven J.B. Cooper; Andrew D. Austin (Science of The Total Environment, 2026)

Synthesis, Characterization, and Use of Magnesium-Activated Biochar for Nitrate Removal from Aqueous Solutions - Nitesh Kasera; Diplina Paul; Praveen Kolar; Steven G. Hall; Sushil Adhikari; Mamun Sarker; Alexander Sinitskii (International Journal of Environmental Research, 2025)
Highlights Premodification of biochar with metal salts can be an effective strategy to prepare effective adsorbents. Extensive physicochemical and structural characterizations were performed to delineate the properties of magnesium-modified biochar. Magnesium improved the physical and surface characteristics of the biochar. Magnesium-loaded biochar demonstrated promising potential as an adsorbent for nitrate. Multiple pathways governed the adsorption mechanism of nitrate on magnesium-loaded biochar.

Vertical green systems (VGSs) and on-site storage for stormwater management - Mojtaba Moravej; Cassady Swinbourne; Rebecca Hall; Steven Kenway (Water Research, 2025)

Enhanced understanding of soil methane processes through modeling microbial kinetics and taxonomy - Shuhao Zhou; Gangsheng Wang; Wenjuan Huang; Kefeng Wang; Liping Zhang; Zehao Lv; Yajing Han; Shanshan Qi; Wei Zhang; Daifeng Xiang; Steven J. Hall (Soil Biology and Biochemistry, 2025)

Utilization of Fish Meal and Fish Oil from Smoked Salmon By-Products in Juvenile Striped Bass (Morone saxatilis) Feeds: Growth Performance, Nutritional Composition, and Shelf-Life Assessment of Upcycled Ingredients - Connor Neagle; Michael O. Frinsko; Ryan Kelly; Steven G. Hall; Benjamin J. Reading; Alexander Chouljenko; Greg Bolton; Michael Joseph (Fishes, 2025)
Fish meal (FM) and fish oil (FO) are vital components commonly used in feed formulations. However, their supply, which generally comes from capture fisheries, is being exhausted, necessitating the exploration of sustainable alternatives. In a two-part study, the first part evaluated the FM and FO derived from smoked salmon by-product (SSBP) over a 12-week accelerated shelf-life test, comparing their lipid oxidation, amino acid, and fatty acid profiles to those of commercial whitefish meal and oil. In the second part, the SSBP FM and FO were then included in three experimental feeds at 25%, 50%, and 100% inclusion levels. These feeds were tested on juvenile striped bass (Morone saxatilis) cultured in a recirculating aquaculture system (RAS). The results indicated that the quality of SSBP FM and FO was lower than the commercial product (less amino acids (23.98% vs. 60.30%) and omega-3 fatty acids (9.46% vs. 26.6%), respectively). SSBP FO exhibited high initial peroxide value (21.00 ± 0.00 meq/kg oil), with gradually increasing total oxidation value and p-Anisidine value during storage. Regarding the feeding trial, all fish showed signs of Mycobacterium marinum infection after one month. While there was no significant difference in feed palatability (p > 0.8559), the feed conversion ratio was less efficient for the 100% SSBP feed (1.44 ± 0.14) compared to commercial feed (1.36 ± 0.13), but these differences were not statistically significant. This study suggests that SSBP FM and FO can be used as supplements at lower levels (25% and 50%) without negatively affecting growth, feed efficiency, or survival. Our findings may be useful for enabling beneficial collaborations between smoked salmon processors, feed manufacturers, and striped bass farmers, therefore contributing to sustainability in aquaculture practices.

Microbial taxa and interactions can predict lignin mineralization in soil at continental scale - Wenjuan Yu; Wenjuan Huang; Kenneth E. Hammel; Yan Li; Shanshan Zhang; Bo Yi; Vitaliy I. Timokhin; Chaoqun Lu; Adina Howe; Samantha R. Weintraub-Leff; Steven J. Hall (Soil Biology and Biochemistry, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Iron‐Driven Fast Decomposition of Soil Carbon Under Periodic Anoxia - Ting Liu; Xin Wang; Simin Wang; Erxiong Zhu; Steven J. Hall; Xiaojuan Feng (Global Change Biology, 2025)
Soil organic carbon (SOC) decomposition underpins soil‐atmosphere carbon exchange and is regulated by climate change‐mediated variations in soil redox conditions. Periodic anoxia, commonly occurring following precipitation, soil flooding, and erosion events, is assumed to preserve SOC. Yet, water saturation may also increase SOC decomposition relative to unsaturated conditions, and contradictory findings among previous studies remain unexplained. Here, using incubation experiments on 20 soils collected across a 24° latitude gradient in China, we show that 70% of the soils showed a higher or similar anoxic decomposition rate of SOC compared to the oxic treatment, indicating fast SOC loss under relatively short anoxia. Methane production was far lower than CO 2 due to the presence of alternative terminal electron acceptors (TEAs). Variation in alternative TEAs and microbial community shows that fast anoxic decomposition was primarily driven by iron (Fe) reduction, which accounted for up to 90% of anoxic CO 2 production. Meanwhile, positive relationships among water‐extractable organic carbon (OC), hydrochloric acid‐extractable ferrous Fe, relative abundance of Fe‐reducing prokaryotes, and the SOC decomposition rate suggest the release of readily metabolized substrates following Fe reduction. This release provided substrates for anoxic metabolism and potentially led to the loss of OC protected by Fe (Fe‐bound OC; a slow‐cycling OC pool under oxic conditions). Mass balance calculation confirms that Fe‐bound OC loss was mostly similar to elevated anoxic SOC decomposition in magnitude, and random forest modeling indicates that soils rich in reducible Fe, SOC, and Fe‐reducing prokaryotes most likely experience elevated SOC decomposition under periodic anoxia. Overall, our findings demonstrate that fast anoxic decomposition of SOC is a potentially important pathway that may stimulate SOC loss under climate change‐mediated intense hydrologic regimes, particularly for soils rich in reducible Fe and SOC.

Increased Cold Tolerance of a Tropical Fish Species at the Northern Edge of Its Expanded Range - Brittany J. Hall-Scharf; Quenton M. Tuckett; Philip W. Stevens; Jeffrey E. Hill (Estuaries and Coasts, 2025)

Influence of extruded soybean meal with different fat contents and varying oleic acid content on floating fish feed quality and composition - Danny B. Patiño; Ondulla T. Toomer; Thien C. Vu; Edgar O. Oviedo-Rondon; Rouf Mian; Mike Frinsko; Steven Hall; Ryan Kelly; Jason Mann; Michael Joseph (Animal Feed Science and Technology, 2024)

Mitigating water pollution: tourists’ willingness to pay for eco-friendly toilets in the Sagarmatha National Park, Mt. Everest area, Nepal - Steven R. Hall; Kirsten Nicholson; Misa Nishikawa (Environment, Development and Sustainability, 2024)

Highly dynamic evolution of the chemosensory system driven by gene gain and loss across subterranean beetles - Pau Balart-García; Tessa M. Bradford; Perry G. Beasley-Hall; Slavko Polak; Steven J.B. Cooper; Rosa Fernández (Molecular Phylogenetics and Evolution, 2024)

Inherited terrestrial cosmogenic nuclides in landscapes of selective glacial erosion: lessons from Lochnagar, Eastern Grampian Mountains, Scotland - Adrian M. Hall; David E. Sugden; Steven A. Binnie; Andy Hein; Tibor Dunai; Benedikt Ritter; Margaret Stewart (Journal of Quaternary Science, 2024)
Inheritance from prior exposure often complicates the interpretation of terrestrial cosmogenic nuclide (TCN) inventories in glaciated terrain. Lochnagar, a mountain in eastern Scotland, holds a clear geomorphological record of corrie glaciation and the thinning of the last Scottish ice sheet over the last ~15 ka. Yet attempts to date the main stages in deglaciation after sampling of 21 granite boulders for 10 Be, 26 Al and 14 C from corrie moraines, an ice sheet lateral moraine and boulder spreads revealed widespread, but variable, TCN inheritance. Only the youngest boulder ages fit within the range of expected deglaciation ages. To identify the sources of geological uncertainty, we provide simple models of ice cover duration and erosion histories for plateau, corrie and strath landscape domains, identify the variable nuclide inheritance that derives from different sources for boulders in these domains, and outline the effects of rotation, splitting and erosion of boulders during glacial transport. The combined effects increase clustering around arbitrary mean TCN values that exceed deglaciation ages. A further implication is that boulders have survived beneath overriding ice sheets. Such boulder trapping at Lochnagar may have resulted from topographic controls on katabatic winds and surface ablation acting on a thinning, cold‐based ice sheet.

Active debris removal: A review and case study on LEOPARD Phase 0-A mission - Mithun Poozhiyil; Manu H. Nair; Mini C. Rai; Alexander Hall; Connor Meringolo; Mark Shilton; Steven Kay; Danilo Forte; Martin Sweeting; Nikki Antoniou; Victoria Irwin (Advances in Space Research, 2023)

Resolving the influence of lignin on soil organic matter decomposition with mechanistic models and continental‐scale data - Bo Yi; Chaoqun Lu; Wenjuan Huang; Wenjuan Yu; Jihoon Yang; Adina Howe; Samantha R. Weintraub‐Leff; Steven J. Hall (Global Change Biology, 2023)
Confidence in model estimates of soil CO 2 flux depends on assumptions regarding fundamental mechanisms that control the decomposition of litter and soil organic carbon (SOC). Multiple hypotheses have been proposed to explain the role of lignin, an abundant and complex biopolymer that may limit decomposition. We tested competing mechanisms using data‐model fusion with modified versions of the CN‐SIM model and a 571‐day laboratory incubation dataset where decomposition of litter, lignin, and SOC was measured across 80 soil samples from the National Ecological Observatory Network. We found that lignin decomposition consistently decreased over time in 65 samples, whereas in the other 15 samples, lignin decomposition subsequently increased. These “lagged‐peak” samples can be predicted by low soil pH, high extractable Mn, and fungal community composition as measured by ITS PC2 (the second principal component of an ordination of fungal ITS amplicon sequences). The highest‐performing model incorporated soil biogeochemical factors and daily dynamics of substrate availability (labile bulk litter:lignin) that jointly represented two hypotheses (C substrate limitation and co‐metabolism) previously thought to influence lignin decomposition. In contrast, models representing either hypothesis alone were biased and underestimated cumulative decomposition. Our findings reconcile competing hypotheses of lignin decomposition and suggest the need to precisely represent the role of lignin and consider soil metal and fungal characteristics to accurately estimate decomposition in Earth‐system models.

Antimicrobial Effects of Plasma-Activated Simulated Seawater (PASW) on Total Coliform and Escherichia coli in Live Oysters during Static Depuration - Vashti M. Campbell; Steven Hall; Deepti Salvi (Fishes, 2023)
Recently, our in vitro study on the effects of plasma-activated simulated seawater (PASW) demonstrated its potential as a novel, alternative disinfectant in oyster depuration. In this current study, PASW’s physicochemical and antimicrobial properties were identified and its effects on oyster quality were observed. Simulated seawater (SS) activated by plasma for 10 min (PASW10) increased in temperature, oxidation reduction potential, and electrical conductivity with a decrease in those parameters after 1:1 dilution with SS (PASW10 (1:1)). The pH decreased immediately after plasma activation and subsequently increased after dilution. Nitrate and nitrite concentrations were higher in PASW10 (1:1) compared to PASW10 (3:1). No free available chlorine was detected in undiluted PASW10. Processing using SS and PASW10 (1:1) depuration and refrigeration of E. coli-bioaccumulated oysters was observed. Significantly higher reductions in total coliform and E. coli were noted for PASW10 (1:1) treated oyster samples after 24 h compared to refrigerated samples. No significant differences in values for condition index or biting force of oyster meats were observed for the processed samples after 24 h. Overall, the novel and environment-friendly PASW could be used as an alternative antimicrobial disinfectant in oyster depuration systems because it does not negatively affect an oyster’s viability or quality.

Nature dependent tourism – Combining big data and local knowledge - Mark D. Spalding; Kate Longley-Wood; Valerie Pietsch McNulty; Sherry Constantine; Montserrat Acosta-Morel; Val Anthony; Aaron D. Cole; Giselle Hall; Barry A. Nickel; Steven R. Schill; Peter W. Schuhmann; Darren Tanner (Journal of Environmental Management, 2023)

Extreme low-flow conditions in a dual-chamber denitrification bioreactor contribute to pollution swapping with low landscape-scale impact - Lindsey M. Hartfiel; Natasha L. Hoover; Steven J. Hall; Thomas M. Isenhart; Carmen L. Gomes; Michelle L. Soupir (Science of The Total Environment, 2023)

Stability of patch‐turnover relationships under equilibrium and nonequilibrium metapopulation dynamics driven by biogeography - Steven R. Beissinger; Sean M. Peterson; Laurie A. Hall; Nathan Van Schmidt; Jerry Tecklin; Benjamin B. Risk; Orien M. Richmond; Tony J. Kovach; A. Marm Kilpatrick (Ecology Letters, 2022)
Two controversial tenets of metapopulation biology are whether patch quality and the surrounding matrix are more important to turnover (colonisation and extinction) than biogeography (patch area and isolation) and whether factors governing turnover during equilibrium also dominate nonequilibrium dynamics. We tested both tenets using 18 years of surveys for two secretive wetland birds, black and Virginia rails, during (1) a period of equilibrium with stable occupancy and (2) after drought and arrival of West Nile Virus (WNV), which resulted in WNV infections in rails, increased extinction and decreased colonisation probabilities modified by WNV, nonequilibrium dynamics for both species and occupancy decline for black rails. Area (primarily) and isolation (secondarily) drove turnover during both stable and unstable metapopulation dynamics, greatly exceeding the effects of patch quality and matrix conditions. Moreover, slopes between turnover and patch characteristics changed little between equilibrium and nonequilibrium, confirming the overriding influences of biogeographic factors on turnover.

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Components of the Female Sex Pheromone of the Newly-Described Canola Flower Midge, Contarinia brassicola - Daniel P. Bray; David R. Hall; Steven J. Harte; Dudley I. Farman; Meghan A. Vankosky; Boyd A. Mori (Journal of Chemical Ecology, 2022)
The canola flower midge, Contarinia brassicola Sinclair (Diptera: Cecidomyiidae), is a newly-described species that induces galls on canola, Brassica napus Linnaeus and Brassica rapa Linnaeus (Brassicaceae). Identification of the sex pheromone of C. brassicola is essential to developing monitoring tools to elucidate the geographic range and hosts of this new pest, and the extent to which it threatens the $30 billion Canadian canola industry. The aim of this study was to identify and synthesize the female-produced sex pheromone of C. brassicola and demonstrate its effectiveness in attracting males to traps in the field. Two peaks were identified through GC-EAG analysis of female-produced volatiles which elicited electrophysiological responses in male antennae. These peaks were initially characterized through GC–MS and synthesis as 2,7-diacetoxynonane (major component) and 2-acetoxynonane (minor component), and the racemic compounds elicited EAG responses in male antennae. All four stereoisomers of 2,7-diacetoxynonane were synthesized and the naturally-produced compound was shown to be primarily the (2 R, 7 S )-isomer by analysis on an enantioselective GC column, with a small amount of (2 R, 7 R )-2,7-diacetoxynonane also present. The configuration of the minor component could not be determined because of the small amount present, but this was assumed to be (2 R )-2-acetoxynonane by comparison with the configuration of the other two components. In field trials, none of the four stereoisomers of 2,7-diacetoxynonane, presented individually or as a racemic mixture, was attractive to male C. brassicola . However, dispensers loaded with a 10 µg:1 µg blend of (2 R, 7 S )- and (2 R, 7 R )-2,7-diacetoxynonane caught large numbers of male C. brassicola and significantly more than other blends tested. The addition of 0.5 µg of (2 R )-2-acetoxynonane to this blend further increased the number of males caught. In future work, we will seek to identify the optimum trapping protocol for the application of the pheromone in monitoring and surveillance.

Identification of Components of the Aggregation Pheromone of the Guam Strain of Coconut Rhinoceros Beetle, Oryctes rhinoceros, and Determination of Stereochemistry - David R. Hall; Steven J. Harte; Dudley I. Farman; Mark Ero; Alfred Pokana (Journal of Chemical Ecology, 2022)
The coconut rhinoceros beetle, Oryctes rhinoceros (Linnaeus 1758) (Coleoptera: Scarabaeidae: Dynastinae) (CRB), is endemic to tropical Asia where it damages both coconut and oil palm. A new invasion by CRB occurred on Guam in 2007 and eradication attempts failed using commonly applied Oryctes rhinoceros nudivirus (OrNV) isolates. This and subsequent invasive outbreaks were found to have been caused by a previously unrecognized haplotype, CRB-G, which appeared to be tolerant to OrNV. The male-produced aggregation pheromone of the endemic, susceptible strain of O. rhinoceros (CRB-S) was previously identified as ethyl 4-methyloctanoate. Following reports from growers that commercial lures containing this compound were not attractive to CRB-G, the aim of this work was to identify the pheromone of CRB-G. Initial collections of volatiles from virgin male and female CRB-G adults from the Solomon Islands failed to show any male- or female-specific compounds as candidate pheromone components. Only after five months were significant quantities of ethyl 4-methyloctanoate and 4-methyloctanoic acid produced by males but not by females. No other male-specific compounds could be detected, in particular methyl 4-methyloctanoate, 4-methyl-1-octanol, or 4-methyl-1-octyl acetate, compounds identified in volatiles from some other species of Oryctes . Ethyl 4-methyloctanoate elicited a strong electroantennogram response from both male and female CRB-G, but these other compounds, including 4-methyloctanoic acid, did not. The enantiomers of ethyl 4-methyloctanoate and 4-methyloctanoic acid were conveniently prepared by enzymatic resolution of the commercially-available acid, and the enantiomers of the acid, but not the ester, could be separated by gas chromatography on an enantioselective cyclodextrin phase. Using this approach, both ethyl 4-methyloctanoate and 4-methyloctanoic acid produced by male CRB-G were shown to be exclusively the ( R )-enantiomers whereas previous reports had suggested male O. rhinoceros produced the ( S )-enantiomers. However, re-examination of the ester and acid produced by male CRB-S from Papua New Guinea showed that these were also the ( R )-enantiomers. In field trapping experiments carried out in the Solomon Islands, both racemic and ethyl ( R )-4-methyloctanoate were highly attractive to both male and female CRB-G beetles. The ( S )-enantiomer and the corresponding acids were only weakly attractive. The addition of racemic 4-methyloctanoic acid to ethyl 4-methyloctanoate did significantly increase attractiveness, but the addition of ( R )- or ( S )-4-methyloctanoic acid to the corresponding ethyl esters did not. Possible reasons for the difference in assignment of configuration of the components of the CRB pheromone are discussed along with the practical implications of these results.

Warming Stimulates Iron-Mediated Carbon and Nutrient Cycling in Mineral-Poor Peatlands - Holly J. Curtinrich; Stephen D. Sebestyen; Natalie A. Griffiths; Steven J. Hall (Ecosystems, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

High carbon losses from oxygen‐limited soils challenge biogeochemical theory and model assumptions - Wenjuan Huang; Kefeng Wang; Chenglong Ye; William C. Hockaday; Gangsheng Wang; Steven J. Hall (Global Change Biology, 2021)
Oxygen (O 2 ) limitation contributes to persistence of large carbon (C) stocks in saturated soils. However, many soils experience spatiotemporal O 2 fluctuations impacted by climate and land‐use change, and O 2 ‐mediated climate feedbacks from soil greenhouse gas emissions remain poorly constrained. Current theory and models posit that anoxia uniformly suppresses carbon (C) decomposition. Here we show that periodic anoxia may sustain or even stimulate decomposition over weeks to months in two disparate soils by increasing turnover and/or size of fast‐cycling C pools relative to static oxic conditions, and by sustaining decomposition of reduced organic molecules. Cumulative C losses did not decrease consistently as cumulative O 2 exposure decreased. After >1 year, soils anoxic for 75% of the time had similar C losses as the oxic control but nearly threefold greater climate impact on a CO 2 ‐equivalent basis (20‐year timescale) due to high methane (CH 4 ) emission. A mechanistic model incorporating current theory closely reproduced oxic control results but systematically underestimated C losses under O 2 fluctuations. Using a model‐experiment integration (ModEx) approach, we found that models were improved by varying microbial maintenance respiration and the fraction of CH 4 production in total C mineralization as a function of O 2 availability. Consistent with thermodynamic expectations, the calibrated models predicted lower microbial C‐use efficiency with increasing anoxic duration in one soil; in the other soil, dynamic organo‐mineral interactions implied by our empirical data but not represented in the model may have obscured this relationship. In both soils, the updated model was better able to capture transient spikes in C mineralization that occurred following anoxic–oxic transitions, where decomposition from the fluctuating‐O 2 treatments greatly exceeded the control. Overall, our data‐model comparison indicates that incorporating emergent biogeochemical properties of soil O 2 variability will be critical for effectively modeling C‐climate feedbacks in humid ecosystems.

Response to “Connectivity and pore accessibility in models of soil carbon cycling” - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2021)
Here we respond to Baveye and colleagues' recent critique of our PROMISE model, describing how this new framework significantly advances our understanding of soil spatial heterogeneity and its influence on organic matter transformations.

Developing a Precautionary Management Approach for the Eastern Canada-West Greenland Population of Bowhead Whales (Balaena mysticetus) - Steven H. Ferguson; Jeff W. Higdon; Patricia A. Hall; Rikke Guldborg Hansen; Thomas Doniol-Valcroze (Frontiers in Marine Science, 2021)
Bowhead whales ( Balaena mysticetus L., 1758) of the Eastern Canada-West Greenland population have been hunted by Inuit for millennia. Significant commercial harvests, conducted by European and American whalers for about 400 years, ended ca. 1915. A small co-managed subsistence harvest from this population has occurred inconsistently in Canada and Greenland, since 1996 and 2009, respectively. Since near extirpation from commercial whaling, population size has increased and the Inuit subsistence hunt now requires a harvest management framework that incorporates knowledge of abundance trends, population dynamics, and carrying capacity. Here, we use a model estimate of pre-commercial exploitation abundance to approximate carrying capacity and develop a management framework with reference points and corresponding stock status zones. When applied to recent abundance estimates, our framework indicates that the population is likely within the healthy (N 50 –N 70 ) zone. Thus, an appropriate management objective is to support continued population increase, with concurrent marginal harvesting, while maintaining the population level above the target reference point (N 70 ) of ca 12,000 whales. However, there remains large uncertainty about current population size and growth rate. The resulting data gaps require a plan for future research to monitor this population in the context of climate changes.

Hydrodynamic Focusing-Enabled Blood Vessel Fabrication for in Vitro Modeling of Neural Surrogates - Kyle A. DiVito; Jason Luo; Katherine E. Rogers; Sumati Sundaram; Steven Roberts; Bibha Dahal; Monique Van Hoek; Kylene Kehn-Hall; James B. Delehanty; André A. Adams (Journal of Medical and Biological Engineering, 2021)

Response to ‘Stochastic and deterministic interpretation of pool models’ - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2021)

Hero Turned Villain: Identification of Components of the Sex Pheromone of the Tomato Bug, Nesidiocoris tenuis - David R. Hall; Steven J. Harte; Daniel P. Bray; Dudley I. Farman; Rob James; Celine X. Silva; Michelle T. Fountain (Journal of Chemical Ecology, 2021)
Nesidiocoris tenuis (Reuter) (Heteroptera: Miridae) is a tropical mirid bug used as a biocontrol agent in protected crops, including tomatoes. Although N. tenuis predates important insect pests, especially whitefly, it also causes damage by feeding on tomato plants when prey populations decline, resulting in significant economic losses for growers. The pest is now established in some all-year-round tomato crops in Europe and control measures involve the application of pesticides which are incompatible with current IPM programs. As part of future IPM strategies, the pheromone of N. tenuis was investigated. Volatile collections were made from groups and individuals of mated and unmated, females and males. In analyses of these collections by gas chromatography coupled with electroantennographic (EAG) recording from antennae of male bugs, two EAG-active components were detected and identified as 1-octanol and octyl hexanoate. Unlike other mirids, both male and female N. tenuis produced the two compounds, before and after mating, and both sexes gave EAG responses to both compounds. Furthermore, only octyl hexanoate was detected in whole body solvent washes from both sexes. These compounds are not related to the derivatives of 3-hydroxybutyrate esters found as pheromone components in other members of the Bryocrinae sub-family, and the latter could not be detected in volatiles from N. tenuis and did not elicit EAG responses. Nevertheless, experiments carried out in commercial glasshouses showed that traps baited with a blend of the synthetic pheromone components caught essentially only male N. tenuis , and significantly more than traps baited with octyl hexanoate alone. The latter caught significantly more N. tenuis than unbaited traps which generally caught very few bugs. Traps at plant height caught more N. tenuis males than traps 1 m above or at the base of the plants. The trap catches provided an indication of population levels of N. tenuis and were greatly reduced following an application of insecticide.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

From pools to flow: The PROMISE framework for new insights on soil carbon cycling in a changing world - Bonnie G. Waring; Benjamin N. Sulman; Sasha Reed; A. Peyton Smith; Colin Averill; Courtney A. Creamer; Daniela F. Cusack; Steven J. Hall; Julie D. Jastrow; Andrea Jilling; Kenneth M. Kemner; Markus Kleber; et al. (Global Change Biology, 2020)
Soils represent the largest terrestrial reservoir of organic carbon, and the balance between soil organic carbon (SOC) formation and loss will drive powerful carbon‐climate feedbacks over the coming century. To date, efforts to predict SOC dynamics have rested on pool‐based models, which assume classes of SOC with internally homogenous physicochemical properties. However, emerging evidence suggests that soil carbon turnover is not dominantly controlled by the chemistry of carbon inputs, but rather by restrictions on microbial access to organic matter in the spatially heterogeneous soil environment. The dynamic processes that control the physicochemical protection of carbon translate poorly to pool‐based SOC models; as a result, we are challenged to mechanistically predict how environmental change will impact movement of carbon between soils and the atmosphere. Here, we propose a novel conceptual framework to explore controls on belowground carbon cycling: P robabilistic R epresentation of O rganic M atter I nteractions within the S oil E nvironment (PROMISE). In contrast to traditional model frameworks, PROMISE does not attempt to define carbon pools united by common thermodynamic or functional attributes. Rather, the PROMISE concept considers how SOC cycling rates are governed by the stochastic processes that influence the proximity between microbial decomposers and organic matter, with emphasis on their physical location in the soil matrix. We illustrate the applications of this framework with a new biogeochemical simulation model that traces the fate of individual carbon atoms as they interact with their environment, undergoing biochemical transformations and moving through the soil pore space. We also discuss how the PROMISE framework reshapes dialogue around issues related to SOC management in a changing world. We intend the PROMISE framework to spur the development of new hypotheses, analytical tools, and model structures across disciplines that will illuminate mechanistic controls on the flow of carbon between plant, soil, and atmospheric pools.

Resolving a paradox—high mercury deposition, but low bioaccumulation in northeastern Puerto Rico - James B. Shanley; Mark Marvin-DiPasquale; Oksana Lane; Wayne Arendt; Steven Hall; William H. McDowell (Ecotoxicology, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Interactive global change factors mitigate soil aggregation and carbon change in a semi‐arid grassland - Tongshuo Bai; Peng Wang; Steven J. Hall; Fuwei Wang; Chenglong Ye; Zhen Li; Shijie Li; Luyao Zhou; Yunpeng Qiu; Jiuxin Guo; Hui Guo; Yi Wang; et al. (Global Change Biology, 2020)
The ongoing global change is multi‐faceted, but the interactive effects of multiple drivers on the persistence of soil carbon (C) are poorly understood. We examined the effects of warming, reactive nitrogen (N) inputs (12 g N m −2 year −1 ) and altered precipitation (+ or − 30% ambient) on soil aggregates and mineral‐associated C in a 4 year manipulation experiment with a semi‐arid grassland on China's Loess Plateau. Our results showed that in the absence of N inputs, precipitation additions significantly enhanced soil aggregation and promoted the coupling between aggregation and both soil fungal biomass and exchangeable Mg 2+ . However, N inputs negated the promotional effects of increased precipitation, mainly through suppressing fungal growth and altering soil pH and clay‐Mg 2+ ‐OC bridging. Warming increased C content in the mineral‐associated fraction, likely by increasing inputs of root‐derived C, and reducing turnover of existing mineral‐associated C due to suppression of fungal growth and soil respiration. Together, our results provide new insights into the potential mechanisms through which multiple global change factors control soil C persistence in arid and semi‐arid grasslands. These findings suggest that the interactive effects among global change factors should be incorporated to predict the soil C dynamics under future global change scenarios.

Lignin lags, leads, or limits the decomposition of litter and soil organic carbon - Steven J. Hall; Wenjuan Huang; Vitaliy I. Timokhin; Kenneth E. Hammel, (Ecology, 2020)
Lignin’s role in litter and soil organic carbon (SOC) decomposition remains contentious. Lignin decomposition was traditionally thought to increase during midstage litter decomposition, when cellulose occlusion by lignin began to limit mass loss. Alternatively, lignin decomposition could be greatest in fresh litter as a consequence of co‐metabolism, and lignin might decompose faster than bulk SOC. To test these competing hypotheses, we incubated 10 forest soils with C 4 grass litter (amended with 13 C‐labeled or unlabeled lignin) over 2 yr and measured soil respiration and its isotope composition. Early lignin decomposition was greatest in 5 of 10 soils, consistent with the co‐metabolism hypothesis. However, lignin decomposition peaked 6–24 months later in the other five soils, consistent with the substrate‐limitation hypothesis; these soils were highly acidic. Rates of lignin, litter, and SOC decomposition tended to converge over time. Cumulative lignin decomposition was never greater than SOC decomposition; lignin decomposition was significantly lower than SOC decomposition in six soils. Net nitrogen mineralization predicted lignin decomposition ratios relative to litter and SOC. Although the onset of lignin decomposition can indeed be rapid, lignin still presents a likely bottleneck in litter and SOC decomposition, meriting a reconsideration of lignin’s role in modern decomposition paradigms.

Lower soil carbon stocks in exotic vs. native grasslands are driven by carbonate losses - Brian Wilsey; Xia Xu; H. Wayne Polley; Kirsten Hofmockel; Steven J. Hall (Ecology, 2020)
Global change includes invasion by exotic (nonnative) plant species and altered precipitation patterns, and these factors may affect terrestrial carbon (C) storage. We measured soil C changes in experimental mixtures of all exotic or all native grassland plant species under two levels of summer drought stress (0 and +128 mm). After 8 yr, soils were sampled in 10‐cm increments to 100‐cm depth to determine if soil C differed among treatments in deeper soils. Total soil C (organic + inorganic) content was significantly higher under native than exotic plantings, and differences increased with depth. Surprisingly, differences after 8 yr in C were due to carbonate and not organic C fractions, where carbonate was ~250 g C/m 2 lower to 1‐m soil depth under exotic than native plantings. Our results indicate that soil carbonate is an active pool and can respond to differences in plant species traits over timescales of years. Significant losses of inorganic C might be avoided by conserving native grasslands in subhumid ecosystems.

Trade‐offs in soil carbon protection mechanisms under aerobic and anaerobic conditions - Wenjuan Huang; Chenglong Ye; William C. Hockaday; Steven J. Hall (Global Change Biology, 2020)
Oxygen (O 2 ) limitation is generally understood to suppress oil carbon (C) decomposition and is a key mechanism impacting terrestrial C stocks under global change. Yet, O 2 limitation may differentially impact kinetic or thermodynamic versus physicochemical C protection mechanisms, challenging our understanding of how soil C may respond to climate‐mediated changes in O 2 dynamics. Although O 2 limitation may suppress decomposition of new litter C inputs, release of physicochemically protected C due to iron (Fe) reduction could potentially sustain soil C losses. To test this trade‐off, we incubated two disparate upland soils that experience periodic O 2 limitation—a tropical rainforest Oxisol and a temperate cropland Mollisol—with added litter under either aerobic (control) or anaerobic conditions for 1 year. Anoxia suppressed total C loss by 27% in the Oxisol and by 41% in the Mollisol relative to the control, mainly due to the decrease in litter‐C decomposition. However, anoxia sustained or even increased decomposition of native soil‐C (11.0% vs. 12.4% in the control for the Oxisol and 12.5% vs. 5.3% in the control for the Mollisol, in terms of initial soil C mass), and it stimulated losses of metal‐ or mineral‐associated C. Solid‐state 13 C nuclear magnetic resonance spectroscopy demonstrated that anaerobic conditions decreased protein‐derived C but increased lignin‐ and carbohydrate‐C relative to the control. Our results indicate a trade‐off between physicochemical and kinetic/thermodynamic C protection mechanisms under anaerobic conditions, whereby decreased decomposition of litter C was compensated by more extensive loss of mineral‐associated soil C in both soils. This challenges the common assumption that anoxia inherently protects soil C and illustrates the vulnerability of mineral‐associated C under anaerobic events characteristic of a warmer and wetter future climate.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Do corn-soybean rotations enhance decomposition of soil organic matter? - Steven J. Hall; Ann E. Russell; A’lece R. Moore (Plant and Soil, 2019)

Floral Odors and the Interaction between Pollinating Ceratopogonid Midges and Cacao - Sarah E. J. Arnold; Samantha J. Forbes; David R. Hall; Dudley I. Farman; Puran Bridgemohan; Gustavo R. Spinelli; Daniel P. Bray; Garvin B. Perry; Leroy Grey; Steven R. Belmain; Philip C. Stevenson (Journal of Chemical Ecology, 2019)
Most plant species depend upon insect pollination services, including many cash and subsistence crops. Plants compete to attract those insects using visual cues and floral odor which pollinators associate with a reward. The cacao tree, Theobroma cacao , has a highly specialized floral morphology permitting pollination primarily by Ceratopogonid midges. However, these insects do not depend upon cacao flowers for their life cycle, and can use other sugar sources. To understand how floral cues mediate pollination in cacao we developed a method for rearing Ceratopogonidae through several complete lifecycles to provide material for bioassays. We carried out collection and analysis of cacao floral volatiles, and identified a bouquet made up exclusively of saturated and unsaturated, straight-chain hydrocarbons, which is unusual among floral odors. The most abundant components were tridecane, pentadecane, ( Z )-7-pentadecene and ( Z )-8-heptadecene with a heptadecadiene and heptadecatriene as minor components. We presented adult midges, Forcipomyia sp. (subgen . Forcipomyia ) , Culicoides paraensis and Dasyhelea borgmeieri, with natural and synthetic cacao flower odors in choice assays. Midges showed weak attraction to the complete natural floral odor in the assay, with no significant evidence of interspecific differences. This suggests that cacao floral volatiles play a role in pollinator behavior. Midges were not attracted to a synthetic blend of the above four major components of cacao flower odor, indicating that a more complete blend is required for attraction. Our findings indicate that cacao pollination is likely facilitated by the volatile blend released by flowers, and that the system involves a generalized odor response common to different species of Ceratopogonidae.

Internal waves influence the thermal and nutrient environment on a shallow coral reef - Emma C. Reid; Thomas M. DeCarlo; Anne L. Cohen; George T. F. Wong; Steven J. Lentz; Aryan Safaie; Austin Hall; Kristen A. Davis (Limnology and Oceanography, 2019)
Internal waves can influence water properties in coastal ecosystems through the shoreward transport and mixing of subthermocline water into the nearshore region. In June 2014, a field experiment was conducted at Dongsha Atoll in the northern South China Sea to study the impact of internal waves on a coral reef. Instrumentation included a distributed temperature sensing system, which resolved spatially and temporally continuous temperature measurements over a 4‐km cross‐reef section from the lagoon to 50‐m depth on the fore reef. Our observations show that during summer, internal waves shoaling on the shallow atoll regularly transport cold, nutrient‐rich water shoreward, altering near‐surface water properties on the fore reef. This water is transported shoreward of the reef crest by tides, breaking surface waves and wind‐driven flow, where it significantly alters the water temperature and nutrient concentrations on the reef flat. We find that without internal wave forcing on the fore reef, temperatures on the reef flat could be up to 2.0°C ± 0.2°C warmer. Additionally, we estimate a change in degree heating weeks of 0.7°C‐weeks warmer without internal waves, which significantly increases the probability of a more severe bleaching event occurring at Dongsha Atoll. Furthermore, using nutrient samples collected on the fore reef during the study, we estimated that instantaneous onshore nitrate flux is about four‐fold higher with internal waves than without internal waves. This work highlights the importance of internal waves as a physical mechanism shaping the nearshore environment, and likely supporting resilience of the reef.

Hydrodynamic effects on oyster aquaculture systems: a review - Matthew D. Campbell; Steven G. Hall (Reviews in Aquaculture, 2019)
Hydrodynamics (i.e. interactions of fluid motion with solid bodies) affect oyster aquaculture within every phase of farming. Although it has many direct and indirect implications to the success of any particular aquaculture endeavour, hydrodynamics is the least understood of environmental factors affecting oyster growth. As the industry continues to mature, it is imperative that the influence of hydrodynamics on oyster aquaculture is thoroughly understood. Hydrodynamics also interacts with other environmental factors, such as salinity, temperature, turbidity, food supply and oxygen, which affect the health and growth of oysters through mixing and transport. Proper siting and management of aquaculture requires a comprehensive understanding of the hydrodynamics involved and its impact on the culture of oysters. Unfortunately, literature is inconsistent on oyster feeding and growth response to the influence of hydrodynamics. Feeding and growth limiting velocities are reported that range from 1 to above 22 cm s −1 . This is in contrast with thriving oyster reefs in a natural setting that exist and thrive above 15 cm s −1 . Upweller systems have reported bulk velocities that range from 0.5 to 7.1 cm s −1 . In practice, higher current velocities are desirable because they increase delivery of food to the oysters, improve water quality, and enhance dispersal of biodeposits. This paper summarizes the findings of those studies in regard to hydrodynamics and provides suggestions for future work.

An introduction to copper and zinc pollution in macroalgae: for use in remediation and nutritional applications - Alexander W. Geddie; Steven G. Hall (Journal of Applied Phycology, 2019)

Research Priorities to Support Effective Manta and Devil Ray Conservation - Joshua D. Stewart; Fabrice R. A. Jaine; Amelia J. Armstrong; Asia O. Armstrong; Michael B. Bennett; Katherine B. Burgess; Lydie I. E. Couturier; Donald A. Croll; Melissa R. Cronin; Mark H. Deakos; Christine L. Dudgeon; Daniel Fernando; et al. (Frontiers in Marine Science, 2018)

Reconciling multiple impacts of nitrogen enrichment on soil carbon: plant, microbial and geochemical controls - Chenglong Ye; Dima Chen; Steven J. Hall; Shang Pan; Xuebin Yan; Tongshuo Bai; Hui Guo; Yi Zhang; Yongfei Bai; Shuijin Hu (Ecology Letters, 2018)
Impacts of reactive nitrogen (N) inputs on ecosystem carbon (C) dynamics are highly variable, and the underlying mechanisms remain unclear. Here, we proposed a new conceptual framework that integrates plant, microbial and geochemical mechanisms to reconcile diverse and contrasting impacts of N on soil C. This framework was tested using long‐term N enrichment and acid addition experiments in a Mongolian steppe grassland. Distinct mechanisms could explain effects of N on particulate and mineral‐associated soil C pools, potentially explaining discrepancies among previous N addition studies. While plant production predominated particulate C changes, N‐induced soil acidification strongly affected mineral‐associated C through decreased microbial growth and pH‐sensitive associations between iron and aluminium minerals and C. Our findings suggest that effects of N‐induced acidification on microbial respiration and geochemical properties should be included in Earth system models that predict ecosystem C budgets under future N deposition/input scenarios.

Drivers of nitrogen transfer in stream food webs across continents - Beth C. Norman; Matt R. Whiles; Sarah M. Collins; Alexander S. Flecker; Steve K. Hamilton; Sherri L. Johnson; Emma J. Rosi; Linda R. Ashkenas; William B. Bowden; Chelsea L. Crenshaw; Todd Crowl; Walter K. Dodds; et al. (Ecology, 2017)
Studies of trophic‐level material and energy transfers are central to ecology. The use of isotopic tracers has now made it possible to measure trophic transfer efficiencies of important nutrients and to better understand how these materials move through food webs. We analyzed data from thirteen 15 N‐ammonium tracer addition experiments to quantify N transfer from basal resources to animals in headwater streams with varying physical, chemical, and biological features. N transfer efficiencies from primary uptake compartments (PUCs; heterotrophic microorganisms and primary producers) to primary consumers was lower (mean 11.5%, range 100%). Total N transferred (as a rate) was greater in streams with open compared to closed canopies and overall N transfer efficiency generally followed a similar pattern, although was not statistically significant. We used principal component analysis to condense a suite of site characteristics into two environmental components. Total N uptake rates among trophic levels were best predicted by the component that was correlated with latitude, DIN:SRP, GPP:ER, and percent canopy cover. N transfer efficiency did not respond consistently to environmental variables. Our results suggest that canopy cover influences N movement through stream food webs because light availability and primary production facilitate N transfer to higher trophic levels.

Effects of nalfurafine on the reinforcing, thermal antinociceptive, and respiratory-depressant effects of oxycodone: modeling an abuse-deterrent opioid analgesic in rats - E. Andrew Townsend; Jennifer E. Naylor; S. Stevens Negus; Shelley R. Edwards; Hina N. Qureshi; Hunter W. McLendon; Christopher R. McCurdy; Coco N. Kapanda; Jussara M. do Carmo; Fernanda S. da Silva; John E. Hall; Kenneth J. Sufka; et al. (Psychopharmacology, 2017)

Late readvance and rapid final deglaciation of the last ice sheet in the Grampian Mountains, Scotland - Adrian M. Hall; Steven A. Binnie; David Sugden; Tibor J. Dunai; Christina Wood (Journal of Quaternary Science, 2016)
Towards the end of the last glaciation, ice sourced from the western Grampian Mountains of Scotland flowed down Strath Spey to encroach on the northern flanks of the Cairngorm Mountains. The maximum of this late advance and its subsequent retreat is recorded by moraines, ice‐marginal meltwater channels, and kame terraces that can be traced for 60 km along Strath Spey. New cosmogenic 10 Be exposure ages from moraines indicate deglaciation at 15.1 ± 1.1 ka. This timing matches closely the recalibrated mean ages of 14.7 ± 0.7 and 15.2 ± 0.7 ka for the Wester Ross Readvance in the North‐West Highlands. A synchronous readvance of the British–Irish Ice Sheet (BIIS) towards the end of Greenland Stadial 2a (GS‐2a) (16.9–14.7 ka) is indicated. Thereafter active ice retreat from the flanks of Strath Spey was rapid, occurring within the ∼1 ka uncertainty of the cosmogenic exposure ages. We suggest the advance followed the collapse of the marine parts of the BIIS at ∼16 ka due to conditions of increased precipitation occurring at a time of low temperatures. The rapidity of deglaciation may reflect enhanced Föhn effects caused by the ice dome in the western Grampians.

Contrasting soil nitrogen dynamics across a montane meadow and urban lawn in a semi-arid watershed - Steven J. Hall; Michelle A. Baker; Scott B. Jones; John M. Stark; David R. Bowling (Urban Ecosystems, 2016)

Scale-dependent linkages between nitrate isotopes and denitrification in surface soils: implications for isotope measurements and models - Steven J. Hall; Samantha R. Weintraub; David R. Bowling (Oecologia, 2016)

Rare taxa have potential to make metabolic contributions in enhanced biological phosphorus removal ecosystems - Christopher E. Lawson; Blake J. Strachan; Niels W. Hanson; Aria S. Hahn; Eric R. Hall; Barry Rabinowitz; Donald S. Mavinic; William D. Ramey; Steven J. Hallam (Environmental Microbiology, 2015)
Summary Enhanced biological phosphorus removal ( EBPR ) relies on diverse but specialized microbial communities to mediate the cycling and ultimate removal of phosphorus from municipal wastewaters. However, little is known about microbial activity and dynamics in relation to process fluctuations in EBPR ecosystems. Here, we monitored temporal changes in microbial community structure and potential activity across each bioreactor zone in a pilot‐scale EBPR treatment plant by examining the ratio of small subunit ribosomal RNA ( SSU r RNA ) to SSU r RNA gene (r DNA ) over a 120 day study period. Although the majority of operational taxonomic units ( OTUs ) in the EBPR ecosystem were rare, many maintained high potential activities based on SSU r RNA : r DNA ratios, suggesting that rare OTUs contribute substantially to protein synthesis potential in EBPR ecosystems. Few significant differences in OTU abundance and activity were observed between bioreactor redox zones, although differences in temporal activity were observed among phylogenetically cohesive OTUs . Moreover, observed temporal activity patterns could not be explained by measured process parameters, suggesting that other ecological drivers, such as grazing or viral lysis, modulated community interactions. Taken together, these results point towards complex interactions selected for within the EBPR ecosystem and highlight a previously unrecognized functional potential among low abundance microorganisms in engineered ecosystems.

Quantification of phytoplankton bloom dynamics by citizen scientists in urban and peri-urban environments - Eva Pintado Castilla; Davi Gasparini Fernandes Cunha; Fred Wang Fat Lee; Steven Loiselle; Kin Chung Ho; Charlotte Hall (Environmental Monitoring and Assessment, 2015)

Lignin decomposition is sustained under fluctuating redox conditions in humid tropical forest soils - Steven J. Hall; Whendee L. Silver; Vitaliy I. Timokhin; Kenneth E. Hammel (Global Change Biology, 2015)
Lignin mineralization represents a critical flux in the terrestrial carbon (C) cycle, yet little is known about mechanisms and environmental factors controlling lignin breakdown in mineral soils. Hypoxia is thought to suppress lignin decomposition, yet potential effects of oxygen (O 2 ) variability in surface soils have not been explored. Here, we tested the impact of redox fluctuations on lignin breakdown in humid tropical forest soils during ten‐week laboratory incubations. We used synthetic lignins labeled with 13 C in either of two positions (aromatic methoxyl or propyl side chain C β ) to provide highly sensitive and specific measures of lignin mineralization seldom employed in soils. Four‐day redox fluctuations increased the percent contribution of methoxyl C to soil respiration relative to static aerobic conditions, and cumulative methoxyl‐C mineralization was statistically equivalent under static aerobic and fluctuating redox conditions despite lower soil respiration in the latter treatment. Contributions of the less labile lignin C β to soil respiration were equivalent in the static aerobic and fluctuating redox treatments during periods of O 2 exposure, and tended to decline during periods of O 2 limitation, resulting in lower cumulative C β mineralization in the fluctuating treatment relative to the static aerobic treatment. However, cumulative mineralization of both the C β ‐ and methoxyl‐labeled lignins nearly doubled in the fluctuating treatment relative to the static aerobic treatment when total lignin mineralization was normalized to total O 2 exposure. Oxygen fluctuations are thought to be suboptimal for canonical lignin‐degrading microorganisms. However, O 2 fluctuations drove substantial Fe reduction and oxidation, and reactive oxygen species generated during abiotic Fe oxidation might explain the elevated contribution of lignin to C mineralization. Iron redox cycling provides a potential mechanism for lignin depletion in soil organic matter. Couplings between soil moisture, redox fluctuations, and lignin breakdown provide a potential link between climate variability and the biochemical composition of soil organic matter.

Mesozooplankton biomass, abundance and community composition in the Ross Sea and the Pacific sector of the Southern Ocean - Catherine J. Stevens; Evgeny A. Pakhomov; Karen V. Robinson; Julie A. Hall (Polar Biology, 2015)

Scaling categorical spatial data for earth systems models - Jaclyn M. Hall; Caroline G. Staub; Matthew P. Marsik; Forrest R. Stevens; Michael W. Binford (Global Change Biology, 2015)

Ocean acidification through the lens of ecological theory - Brian Gaylord; Kristy J. Kroeker; Jennifer M. Sunday; Kathryn M. Anderson; James P. Barry; Norah E. Brown; Sean D Connell; Sam Dupont; Katharina E. Fabricius; Jason M. Hall-Spencer; Terrie Klinger; Marco Milazzo; et al. (Ecology, 2015)
Ocean acidification, chemical changes to the carbonate system of seawater, is emerging as a key environmental challenge accompanying global warming and other human‐induced perturbations. Considerable research seeks to define the scope and character of potential outcomes from this phenomenon, but a crucial impediment persists. Ecological theory, despite its power and utility, has been only peripherally applied to the problem. Here we sketch in broad strokes several areas where fundamental principles of ecology have the capacity to generate insight into ocean acidification's consequences. We focus on conceptual models that, when considered in the context of acidification, yield explicit predictions regarding a spectrum of population‐ and community‐level effects, from narrowing of species ranges and shifts in patterns of demographic connectivity, to modified consumer–resource relationships, to ascendance of weedy taxa and loss of species diversity. Although our coverage represents only a small fraction of the breadth of possible insights achievable from the application of theory, our hope is that this initial foray will spur expanded efforts to blend experiments with theoretical approaches. The result promises to be a deeper and more nuanced understanding of ocean acidification and the ecological changes it portends.

Breaking the enzymatic latch: impacts of reducing conditions on hydrolytic enzyme activity in tropical forest soils - Steven J. Hall; Jonathan Treffkorn; Whendee L. Silver (Ecology, 2014)
The enzymatic latch hypothesis proposes that oxygen (O 2 ) limitation promotes wetland carbon (C) storage by indirectly decreasing the activities of hydrolytic enzymes that decompose organic matter. Humid tropical forest soils are often characterized by low and fluctuating redox conditions and harbor a large pool of organic matter, yet they also have the fastest decomposition rates globally. We tested the enzymatic latch hypothesis across a soil O 2 gradient in the Luquillo Experimental Forest, Puerto Rico, USA. Enzyme activities expressed on a soil mass basis did not systematically decline across a landscape O 2 gradient, nor did phenolics accumulate, the proposed mechanism of the enzymatic latch. Normalizing enzyme activities by C concentrations did suggest a decline in several enzymes as mean soil O 2 decreased. However, relationships between hydrolytic enzymes and reducing conditions were scale‐dependent: enzymes displayed neutral to strongly positive relationships with reducing conditions and phenolics when comparing samples within sites, and enzyme activities in 18‐d anaerobic incubations generally exceeded those in aerobic soils despite a fourfold increase in phenolics. In summary, although O 2 availability and the activities of some enzymes appeared to be related at landscape scales after accounting for differences in organic matter, reducing conditions and phenolic compounds did not appear to constrain soil hydrolytic enzyme activity at the scale of soil microsites, challenging the enzymatic latch hypothesis. Hydrolytic enzymes can be resilient to periodic anaerobiosis and may actually stimulate O 2 consumption at the microsite scale. We suggest a critical re‐examination of mechanisms and the scale dependence of couplings between O 2 and decomposition in terrestrial soils.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Iron oxidation stimulates organic matter decomposition in humid tropical forest soils - Steven J. Hall; Whendee L. Silver (Global Change Biology, 2013)
Humid tropical forests have the fastest rates of organic matter decomposition globally, which often coincide with fluctuating oxygen ( O 2 ) availability in surface soils. Microbial iron (Fe) reduction generates reduced iron [Fe(II)] under anaerobic conditions, which oxidizes to Fe(III) under subsequent aerobic conditions. We demonstrate that Fe (II) oxidation stimulates organic matter decomposition via two mechanisms: (i) organic matter oxidation, likely driven by reactive oxygen species; and (ii) increased dissolved organic carbon (DOC) availability, likely driven by acidification. Phenol oxidative activity increased linearly with Fe(II) concentrations ( P 0.0001, pseudo R 2 = 0.79) in soils sampled within and among five tropical forest sites. A similar pattern occurred in the absence of soil, suggesting an abiotic driver of this reaction. No phenol oxidative activity occurred in soils under anaerobic conditions, implying the importance of oxidants such as O 2 or hydrogen peroxide ( H 2 O 2 ) in addition to Fe(II). Reactions between Fe(II) and H 2 O 2 generate hydroxyl radical, a strong nonselective oxidant of organic compounds. We found increasing consumption of H 2 O 2 as soil Fe(II) concentrations increased, suggesting that reactive oxygen species produced by Fe(II) oxidation explained variation in phenol oxidative activity among samples. Amending soils with Fe(II) at field concentrations stimulated short‐term C mineralization by up to 270%, likely via a second mechanism. Oxidation of Fe(II) drove a decrease in pH and a monotonic increase in DOC; a decline of two pH units doubled DOC, likely stimulating microbial respiration. We obtained similar results by manipulating soil acidity independently of Fe(II), implying that Fe(II) oxidation affected C substrate availability via pH fluctuations, in addition to producing reactive oxygen species. Iron oxidation coupled to organic matter decomposition contributes to rapid rates of C cycling across humid tropical forests in spite of periodic O 2 limitation, and may help explain the rapid turnover of complex C molecules in these soils.

When Wet Gets Wetter: Decoupling of Moisture, Redox Biogeochemistry, and Greenhouse Gas Fluxes in a Humid Tropical Forest Soil - Steven J. Hall; William H. McDowell; Whendee L. Silver (Ecosystems, 2013)

Biology of Salpa thompsoni in waters adjacent to the Ross Sea, Southern Ocean, during austral summer 2008 - E. A. Pakhomov; J. Hall; M. J. M. Williams; B. P. V. Hunt; C. J. Stevens (Polar Biology, 2011)

Ligand-Binding Mass Spectrometry to Study Biotransformation of Fusion Protein Drugs and Guide Immunoassay Development: Strategic Approach and Application to Peptibodies Targeting the Thrombopoietin Receptor - Michael P. Hall; Colin Gegg; Kenneth Walker; Christopher Spahr; Robert Ortiz; Vimal Patel; Steven Yu; Liana Zhang; Hsieng Lu; Binodh DeSilva; Jean W. Lee (The AAPS Journal, 2010)

Quantifying structural physical habitat attributes using LIDAR and hyperspectral imagery - Robert K. Hall; Russell L. Watkins; Daniel T. Heggem; K. Bruce Jones; Philip R. Kaufmann; Steven B. Moore; Sandra J. Gregory (Environmental Monitoring and Assessment, 2009)

Characterizing dispersal patterns in a threatened seabird with limited genetic structure - LAURIE A. HALL; PER J. PALSBØLL; STEVEN R. BEISSINGER; JAMES T. HARVEY; MARTINE BÉRUBÉ; MARTIN G. RAPHAEL; S. KIM NELSON; RICHARD T. GOLIGHTLY; LAURA MCFARLANE‐TRANQUILLA; SCOTT H. NEWMAN; M. ZACHARIAH PEERY (Molecular Ecology, 2009)
Genetic assignment methods provide an appealing approach for characterizing dispersal patterns on ecological time scales, but require sufficient genetic differentiation to accurately identify migrants and a large enough sample size of migrants to, for example, compare dispersal between sexes or age classes. We demonstrate that assignment methods can be rigorously used to characterize dispersal patterns in a marbled murrelet ( Brachyramphus marmoratus ) population from central California that numbers approximately 600 individuals and is only moderately differentiated ( F ST ∼ 0.03) from larger populations to the north. We used coalescent simulations to select a significance level that resulted in a low and approximately equal expected number of type I and II errors and then used this significance level to identify a population of origin for 589 individuals genotyped at 13 microsatellite loci. The proportion of migrants in central California was greatest during winter when 83% of individuals were classified as migrants compared to lower proportions during the breeding (6%) and post‐breeding (8%) seasons. Dispersal was also biased toward young and female individuals, as is typical in birds. Migrants were rarely members of parent‐offspring pairs, suggesting that they contributed few young to the central California population. A greater number of migrants than expected under equilibrium conditions, a lack of individuals with mixed ancestry, and a small number of potential source populations (two), likely allowed us to use assignment methods to rigorously characterize dispersal patterns for a population that was larger and less differentiated than typically thought required for the identification of migrants.

Relationship between urbanization and bat community structure in national parks of the southeastern U.S. - Susan C. Loeb; Christopher J. Post; Steven T. Hall (Urban Ecosystems, 2009)

Simple three‐pool model accurately describes patterns of long‐term litter decomposition in diverse climates - E. CAROL ADAIR; WILLIAM J. PARTON; STEVEN J. DEL GROSSO; WHENDEE L. SILVER; MARK E. HARMON; SONIA A. HALL; INGRID C. BURKE; STEPHEN C. HART (Global Change Biology, 2008)
As atmospheric CO 2 increases, ecosystem carbon sequestration will largely depend on how global changes in climate will alter the balance between net primary production and decomposition. The response of primary production to climatic change has been examined using well‐validated mechanistic models, but the same is not true for decomposition, a primary source of atmospheric CO 2 . We used the Long‐term Intersite Decomposition Experiment Team (LIDET) dataset and model‐selection techniques to choose and parameterize a model that describes global patterns of litter decomposition. Mass loss was best represented by a three‐pool negative exponential model, with a rapidly decomposing labile pool, an intermediate pool representing cellulose, and a recalcitrant pool. The initial litter lignin/nitrogen ratio defined the size of labile and intermediate pools. Lignin content determined the size of the recalcitrant pool. The decomposition rate of all pools was modified by climate, but the intermediate pool's decomposition rate was also controlled by relative amounts of litter cellulose and lignin (indicative of lignin‐encrusted cellulose). The effect of climate on decomposition was best represented by a composite variable that multiplied a water‐stress function by the Lloyd and Taylor variable Q 10 temperature function. Although our model explained nearly 70% of the variation in LIDET data, we observed systematic deviations from model predictions. Below‐ and aboveground material decomposed at notably different rates, depending on the decomposition stage. Decomposition in certain ecosystem‐specific environmental conditions was not well represented by our model; this included roots in very wet and cold soils, and aboveground litter in N‐rich and arid sites. Despite these limitations, our model may still be extremely useful for global modeling efforts, because it accurately ( R 2 =0.6804) described general patterns of long‐term global decomposition for a wide array of litter types, using relatively minimal climatic and litter quality data.

Does harvesting sustain plant diversity in central Mexican wetlands? - Steven J. Hall; Roberto Lindig-Cisneros; Joy B. Zedler (Wetlands, 2008)

Extent of the last ice sheet in northern Scotland tested with cosmogenic 10 Be exposure ages - William M. Phillips; Adrian M. Hall; Colin K. Ballantyne; Steven Binnie; Peter W. Kubik; Stewart Freeman (Journal of Quaternary Science, 2008)
The extent of the last British–Irish Ice Sheet (BIIS) in northern Scotland is disputed. A restricted ice sheet model holds that at the global Last Glacial Maximum (LGM; ca. 23–19 ka) the BIIS terminated on land in northern Scotland, leaving Buchan, Caithness and the Orkney Islands ice‐free. An alternative model implies that these three areas were ice‐covered at the LGM, with the BIIS extending offshore onto the adjacent shelves. We test the two models using cosmogenic 10 Be surface exposure dating of erratic boulders and glacially eroded bedrock from the three areas. Our results indicate that the last BIIS covered all of northern Scotland during the LGM, but that widespread deglaciation of Caithness and Orkney occurred prior to rapid warming at ca. 14.5 ka. Copyright © 2008 John Wiley & Sons, Ltd.

The effect of copper deficiency on the formation of hemosiderin in sprague-dawley rats - Kevin D. Welch; Jeffery O. Hall; T. Zane Davis; Steven D. Aust (BioMetals, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Effect of Volatile Constituents from Securidaca Longepedunculata on Insect pests Of Stored Grain - Thamara K. Jayasekara; Philip C. Stevenson; David R. Hall; Steven R. Belmain (Journal of Chemical Ecology, 2005)

JUVENILE HORMONE REGULATES DE NOVO ISOPRENOID AGGREGATION PHEROMONE BIOSYNTHESIS IN PINE BARK BEETLES, Ips SPP., THROUGH TRANSCRIPTIONAL CONTROL OF HMG-CoA REDUCTASE - JULIE A. TILLMAN; FANG LU; LANE M. GODDARD; ZOE R. DONALDSON; SILVER C. DWINELL; CLAUS TITTIGER; GREGORY M. HALL; ANDREW J. STORER; GARY J. BLOMQUIST; STEVEN J. SEYBOLD (Journal of Chemical Ecology, 2004)

Potential Beneficial Metabolic Interactions Between Tamoxifen and Isoflavones via Cytochrome P450-mediated Pathways in Female Rat Liver Microsomes - Jun Chen; Steven C. Halls; Joshua F. Alfaro; Zhaohui Zhou; Ming Hu (Pharmaceutical Research, 2004)

Fragmentation of Florida scrub in an urban landscape - Jaclyn M. Hall; Thomas W. Gillespie; Donald Richardson; Steven Reader (Urban Ecosystems, 2002)

Midgut tissue of male pine engraver, Ips pini, synthesizes monoterpenoid pheromone component ipsdienol de novo - Gregory M. Hall; Claus Tittiger; Gracie L. Andrews; Grant S. Mastick; Marilyn Kuenzli; Xin Luo; Steven J. Seybold; Gary J. Blomquist (The Science of Nature, 2002)

EMAP Design and River Reach File 3 (RF3) as a Sample Frame in the Central Valley, California - Robert K. Hall; Anthony Olsen; Donald Stevens; Barbara Rosenbaum; Peter Husby; Gary A. Wolinsky; Daniel T. Heggem (Environmental Monitoring and Assessment, 2000)

Recent advances in solid phase synthesis - Steven E. Hall (Molecular Diversity, 1998)

A Computational Analysis of FXa Generation by TF:FVIIa on the Surface of Rat Vascular Smooth Muscle Cells - Connie L. Hall; Steven M. Slack; Vincent T. Turitto (Annals of Biomedical Engineering, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

The Future of Combinatorial Chemistry as a Drug Discovery Paradigm - Steven E. Hall (Pharmaceutical Research, 1997)

The influence of contaminant and water quality conditions on larval striped bass in the Potomac River and upper Chesapeake Bay in 1990: Anin situ study - Lenwood W. Hall; Michael C. Ziegenfuss; Steven A. Fischer; John A. Sullivan; Deborah M. Palmer (Archives of Environmental Contamination and Toxicology, 1993)

Chromatographic determination of dicofol and metabolites in egg yolks - Charles R. Mourer; Gregory L. Hall; W. Eugene Whitehead; Takayuki Shibamoto; Lee R. Shull; Steven E. Schwarzbach (Archives of Environmental Contamination and Toxicology, 1990)